EFFECTS OF DIFFERENT SOIL TILLAGE SYSTEMS ON NODULATION AND YIELD OF SOYBEAN - D. Jug; Mihaela Blažinkov; S. Redžepović; Irena Jug; B. Stipešević (Poljoprivreda, 2005)
The primary soil tillage for different crops in Croatia is generally based on mouldboard ploughing which is the most expensive for crops production. Negative effects due to frequent passes by equipment and machines (deterioration of soil structure, soil compaction, lower biogenity and soil tilth), together with negative economical and energetical costs, can be lowered and avoided by introduction of reduced soil tillage or direct drilling (No-tillage). Accordingly, the main goal of this research was to determine effects of conventional and reduced soil tillage systems on yield components and nodulation ability of nitrogen fixing bacteria in soybean crop. The research was established at chernozem soil type of northern Baranja as monofactorial completely randomized block design in four repetitions. The soil tillage variants were as follows: CT) Conventional Tillage (primary soil tillage by moldboard ploughing at 25-30 cm depth), DH) Multiple Diskharrowing at 10-15 cm as primary tillage, and NT) No-tillage system. Results show significantly lower plant density, mass of 1000 grains and grain yield at variants with reduced soil tillage in both investigation years. However, reduced tillage systems had positive trend on nitrogen-fixing bacteria nodulation, since the highest values of number and mass of nodules per plant were recorded. This research was run during the years 2002 and 2003, the last one extremely droughty, thus it requires continuation.